Stay : the true story of ten dogs - Muntean, Michaela; Bailey, K. C; Kazmierski, Stephen (New York : Scholastic Press, 2012)
Luciano Anastasini, a man who calls the circus home, and ten homeless dogs are brought together by fate.
School Library Journal, March 2012.
Publisher's Weekly, February 2012.
Kirkus Review, February 2012.
School Library Journal.
Publisher's Weekly.
Kirkus Review.
Keywords: Anastasini, Luciano -- Juvenile literature; Anastasini, Luciano; Anastasini, Luciano; Dog adoption -- Juvenile literature; Circus performers -- Juvenile literature; Dogs -- Behavior -- Juvenile literature; Dog adoption; Circus performers; Dogs -- Behavior; Dog adoption; Circus performers; Dogs -- Behavior; Dog adoption; Circus performers; Dogs -- Behavior